Empirical Studies on Effect of Low-Level Laser Treatment on Glioblastoma Multiforme in Combination with Ag-PMMA-PAA Nanoparticles: Paired Red Region Optical-Property Treatment Platform - Rohini Atluri; Daniel Korir; Tae-Youl Choi; Denise Perry Simmons (Applied Nano, 2022)
Glioblastoma multiforme is an aggressive, invasive, fatal primary heterogenic brain tumor. New treatments have not significantly improved the dismal survival rate. Low-level laser therapy reports indicate different tumor cells respond distinctly to low-level laser therapy based on laser dose (J/cm2) or with nanotherapeutics. We investigated the effects of pairing two optical property-driven treatment agents—a low-level laser on glioblastoma multiforme (U251) using an He-Ne laser (632.8 nm) with 18.8 nm spherical Ag-PMMA-PAA nanoparticles, with an absorbance peak at 400 nm with a broad shoulder to 700 nm. The He-Ne treatment parameters were power (14.87 ± 0.3 mW), beam diameter (0.68 cm), and exposure time 5 min leading to a 12.28 J/cm2 dose. A dose of 12.28 J/cm2 was applied to Ag-PMMA-PAA nanoparticle concentrations (110–225 μM). An amount of 110 μM Ag-PMMA-PAA nanoparticles combined with an He-Ne dose at 18 h yielded 23% U251 death compared to He-Ne alone which yielded 8% U251 death. A 225 μM Ag-PMMA-PAA nanoparticle He-Ne combination resulted in an earlier, more significant, U251 death of 38% at 6 h compared to 30% with 225 μM alone at 18 h. Both treatment agents possess inherent physical and functional properties capable of redesign to enhance the observed cell death effects. Our results provide evidence supporting next-step studies to test “the redesign hypothesis” that these paired optical-driven agents provide a tunable platform that can generate significant U251 cell death increase.